2013
DOI: 10.1161/jaha.113.000361
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Extracellular Signal–Regulated Kinase 2 Suppresses Endoplasmic Reticulum Stress and Protects From Oxidative Stress and Endothelial Dysfunction

Abstract: BackgroundInsulin signaling comprises 2 major cascades: the insulin receptor substrate/phosphatidylinositol 3′‐kinase/protein kinase B and Ras/Raf/mitogen‐activated protein kinase/kinase/ERK pathways. While many studies on the tissue‐specific effects of the insulin receptor substrate/phosphatidylinositol 3′ ‐kinase/protein kinase B pathway have been conducted, the role of the other cascade in tissue‐specific insulin resistance has not been investigated. High glucose/fatty acid toxicity, inflammation, and oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…In contrast, the phenotype of wild-type PPARG was less severe and could be (at least partially) rescued by GRK2 inhibition. Together, these data indicate that the ERK axis may specifically counteract the heart failure-promoting transcription factor Pparg by preventing heart failure-related Pparg target gene induction (36,54) and/or could confer protection against palmitate-induced endoplasmic reticulum stress (55).…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, the phenotype of wild-type PPARG was less severe and could be (at least partially) rescued by GRK2 inhibition. Together, these data indicate that the ERK axis may specifically counteract the heart failure-promoting transcription factor Pparg by preventing heart failure-related Pparg target gene induction (36,54) and/or could confer protection against palmitate-induced endoplasmic reticulum stress (55).…”
Section: Discussionmentioning
confidence: 79%
“…Short-term IH infusion activates ERK1/2 in the liver (data unpublished) and it has been reported that PKCd activates ERK (Ueda et al 1996). It has also been shown that hepatic ERK2 alleviates oxidative stress, probably as a result of attenuated endoplasmic reticulum (ER) stress (Kujiraoka et al 2013). Short-term lipid infusion also activates p38 MAPK (data unpublished), which has also been reported to attenuate ER stress (Lee et al 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Free radicals or ROS create oxidative stress, which leads to a variety of pathological lesions. Research has revealed that high glucose may activate NADPH oxidase and lead to the production of ROS, which can cause endothelial dysfunction and even cell apoptosis [20,21]. Moreover, previous studies have established that oxygen-derived free radicals interfere with or destroy endothelium by inactivating NO in normal vessels [22,23].…”
Section: Discussionmentioning
confidence: 99%